KEPEMIMPINAN DAN STRATEGI DIFERENSIASI DI PT SHOPEE INTERNATIONAL INDONESIA - Arsana Indah Salsabillah; Dini Nur Ardila; Sentot Imam Wahjono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of leadership and differentiation strategy in shaping the competitive advantage of PT Shopee International Indonesia in the increasingly competitive e-commerce industry. Shopee, as one of the leading technology companies in Southeast Asia, has successfully positioned itself as a superior online shopping platform through transformational leadership and innovative differentiation strategies. The research method used is descriptive qualitative with a case study approach by analyzing secondary data from journals, articles, company reports, and indirect interviews from media sources. The results show that the situational leadership style applied by Shopee’s management, especially in responding to the dynamics of millennial and Gen Z generations, fosters an adaptive, collaborative, and results-oriented organizational culture. On the other hand, the differentiation strategy is carried out through free delivery services, user loyalty programs, the Shopee Mall feature, the use of artificial intelligence for personalized user experiences, and integration with social media. This strategy not only increases customer loyalty but also creates added value that is difficult for competitors to imitate. The conclusion of this study states that the synergy between effective leadership and appropriate differentiation strategy can sustainably enhance Shopee’s competitiveness in the Indonesian digital market.